CNGB1‐related rod‐cone dystrophy: A mutation review and update. Issue 6 (16th May 2021) - Nassisi, Marco; Smirnov, Vasily M.; Solis Hernandez, Cyntia; Mohand‐Saïd, Saddek; Condroyer, Christel; Antonio, Aline; Kühlewein, Laura; Kempf, Melanie; Kohl, Susanne; Wissinger, Bernd; Nasser, Fadi; Ragi, Sara D.; et al.
Abstract: Cyclic nucleotide‐gated channel β1 ( CNGB1 ) encodes the 240‐kDa β subunit of the rod photoreceptor cyclic nucleotide‐gated ion channel. Disease‐causing sequence variants in CNGB1 lead to autosomal recessive rod‐cone dystrophy/retinitis pigmentosa (RP). We herein present a comprehensive review and analysis of all previously reported CNGB1 sequence variants, and add 22 novel variants, thereby enlarging the spectrum to 84 variants in total, including 24 missense variants (two of which may also affect splicing), 21 nonsense, 19 splicing defects (7 at noncanonical positions), 10 small deletions, 1 small insertion, 1 small insertion–deletion, 7 small duplications, and 1 gross deletion. According to the American College of Medical Genetics and Genomics classification criteria, 59 variants were considered pathogenic or likely pathogenic and 25 were variants of uncertain significance. In addition, we provide further phenotypic data from 34 CNGB1 ‐related RP cases, which, overall, are in line with previous findings suggesting that this form of RP has long‐term retention of useful central vision despite the early onset of night blindness, which is valuable for patient counseling, but also has implications for it being considered a priority target for gene therapy trials.